Pengembangan Model Diklat Interaksi dan Komunikasi Anak dengan Autisme - Trisno Ikhwanudin (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2017)
This research is motivated by the need for the design and implementation of training model for the development of interaction and communication of children with autism that is effective according to the needs of the institution and the field. The formulation of the problem is "what kind of training model that suits the needs of teacher competence improvement in developing interaction and communication skills of children with autism disorder?". This research uses Research and Development (R & D) model of Dugan Laird model. This research uses purposive sampling which involves all respondents of alumni of related training. Data were analyzed using t-test and qualitative analysis. The conclusions are: (1) based on the result of the test on the data of the alumni of training perception on his own competence and the implementation of the training result in their schools, the result of the test shows that the autistic training conducted in Bandung is more effective than the previous two training, Medan and Semarang training. (2) The resulting training design model is assumed to be more effective than the previous training design because it has the clarity of the program structure and its evaluation system.